An Analysis of 34, 218 Pediatric Outpatient Controlled Substance Prescriptions. (March 2016) - George, Jessica A.; Park, Paul S.; Hunsberger, Joanne; Shay, Joanne E.; Lehmann, Christoph U.; White, Elizabeth D.; Lee, Benjamin H.; Yaster, Myron
Abstract : BACKGROUND: Prescription errors are among the most common types of iatrogenic errors. Because of a previously reported 82% error rate in handwritten discharge narcotic prescriptions, we developed a computerized, web-based, controlled substance prescription writer that includes weight-based dosing logic and alerts to reduce the error rate to (virtually) zero. Over the past 7 years, >34, 000 prescriptions have been created by hospital providers using this platform. We sought to determine the ongoing efficacy of the program in prescription error reduction and the patterns with which providers prescribe controlled substances for children and young adults (ages 0–21 years) at hospital discharge. METHODS: We examined a database of 34, 218 controlled substance discharge prescriptions written by our institutional providers from January 1, 2007 to February 14, 2014, for demographic information, including age and weight, type of medication prescribed based on patient age, formulation of dispensed medication, and amount of drug to be dispensed at hospital discharge. In addition, we randomly regenerated 2% (700) of prescriptions based on stored data and analyzed them for errors using previously established error criteria. Weights that were manually entered into the prescription writer by the prescriber were compared with the patient's weight in the hospital's electronic medical record. RESULTS: Patients in the database averaged 9 ± 6.1 (range, 0–21) years of age and 36.7 ± 24.9 (1–195) kg. Regardless of age, the most commonly prescribed opioid was oxycodone (73%), which was prescribed as a single agent uncombined with acetaminophen. Codeine was prescribed to 7% of patients and always in a formulation containing acetaminophen. Liquid formulations were prescribed to 98% of children <6 years of age and to 16% of children >12 years of age (the remaining 84% received tablet formulations). Regardless of opioid prescribed, the amount of liquid dispensed averaged 106 ± 125 (range, 2–3240) mL, and the number of tablets dispensed averaged 51 ± 51 (range, 1–1080). Of the subset of 700 regenerated prescriptions, all were legible (drug, amount dispensed, dose, patient demographics, and provider name) and used best prescribing practice (e.g., no trailing zero after a decimal point, leading zero for doses <1). Twenty-five of the 700 (3.6%) had incorrectly entered weights compared with the most recent weight in the chart. Of these, 14 varied by 10% or less and only 2 varied by >15%. Of these, 1 resulted in underdosing (true weight 80 kg prescribed for a weight of 50 kg) and the other in overdosing (true weight 10 kg prescribed for a weight of 30 kg). CONCLUSIONS: A computerized prescription writer eliminated most but not all the errors common to handwritten prescriptions. Oxycodone has supplanted codeine as the most commonly prescribed oral opioid in current pediatric pain practice and, independent of formulation, is dispensed in large quantities. This study underscores the need for liquid opioid formulations in the pediatric population and, because of their abuse potential, the urgent need to determine how much of the prescribed medication is actually used by patients. Abstract : Published ahead of print November 17, 2015